Emotion analysis using machine learning model and deep learning model on DEAP dataset - Hasan, Anita; Abrar, Fahim; Sabur, Eshaan Tanzim; Muntasir, Iftehaj; Na sha, Sumaia Sadia (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.